(untitled) (Clinics, 2012)
Multiple endocrine neoplasia (MEN) types 1 and 2 are genetic diseases that are inherited as autosomal traits. The major clinical manifestations of multiple endocrine neoplasia type 1 include the so-called "3 P's": parathyroid, pituitary, and pancreatic tumors, including gastroenteroneuroendocrine tumors. Genetic testing can be performed on patients and the potential carriers of the menin gene mutation, but the genotype-phenotype correlation in multiple endocrine neoplasia type 1 is less straightforward than multiple endocrine neoplasia type 2. Most likely, the main advantage of genetic testing in MEN1 is to exclude from further studies those who are negative for the genetic mutation if they belong to a family with a known history of MEN1. In Chile, we started with rearranged during transfection proto-oncogene genetic testing (MEN2) 15 years ago. We carried out a prophylactic total thyroidectomy to prevent medullary thyroid carcinoma in a three-year-old girl who presented with microscopic medullary thyroid carcinoma. More than 90% of the individuals who tested positive using a genetic test achieved a biochemical cure compared with only 27% of patients who receive a clinical diagnosis. Mutations are mainly located in exon 11; the most common is C634W, rather than C634R. Hypertensive crisis was the cause of death in three patients, and extensive distant metastases occurred in nine (including two patients with multiple endocrine neoplasia type 2B) of 14 patients. Earlier recognition of medullary thyroid carcinoma and the other features of the disease, especially pheochromocytoma, will improve the survival rate of patients with multiple endocrine neoplasia.